Technology of Obtaining Carbon Nanotubes and Their Use in Practice History of Nanotechnology Development - U.D. Sherkulov (Genius Journals, 2024)
Article on the history of development of nanotechnologies, author Uktam Dekhkonovich Sherkulov, Republic of Uzbekistan, Navoi State Pedagogical Institute. The article describes what nanotechnology is, the emergence of nanotube research, the creation of electron microscopes, Feynman's lecture, the results of research by world scientists, and a lot of historical information. The article is intended for scientific researchers and graduate students.
Keywords: Electron microscope; diffusion length of input atoms; atom; assembly